Analisis Antioksidan Ekstrak Etanol Daun Ceguk (Combretum indicum L.) varr.M dengan Berbagai Lokasi Kalimantan Selatan, Indonesia - Samsul Hadi; Umi Nur Hapifah; Amalia Khairunnisa (Institute for Halal Industry and System (IHIS) Universitas Gadjah Mada, 2022)
Indicum has 2 variations, especially in terms of flowers, namely elongated and rounded types with antioxidant effects. So the aim of this research is to know the antioxidant of C. Indicum leaves, one of the varieties in Banjar, Banjarbaru and Tanah Laut areas, that variety is C. indicum varr.M. Antioxidant testing using TLC and quantitative using UV-Vis spectrophotometer. The antioxidant results qualitatively have antioxidant activity marked by a yellowish white stain. The quantitative test results of Banjar, Banjarbaru and Tanah Laut have 97.2219±0.263 ppm, 50.0832±0.078 ppm and 56.2046±0.185 ppm IC50 values. The results of One Way Anova analysis on the ethanol extract of elongated C. indicum leaves from Banjar, Banjarbaru and Tanah Laut had significant differences between each location and other locations. Based on these results Banjarbaru has the best antioxidants.